U–Pb zircon geochronology, petrochemical and Sr–Nd isotopic characteristic of Late Neoproterozoic granitoids of the Bornaward complex (Bardaskan-NE Iran) - Monazzami Bagherzadeh, R. (2015)
The Bornaward granitoids in the Taknar zone are located in the northeast of the central Iranian block in northeast Iran (Khorasan Razavi province), about 280 km southwest of Mashhad city and 28 km northwest of Bardaskan city. Taknar zone is an exotic block, bordered by two major faults, the Great Kavir fault in the south and Rivash fault in the north. Intrusive rocks of the study area, called the Bornaward granitoid complex (BGC), include of granite, alkali granite, syenogranite, leucogranite, granophyre, monzogranite, granodiorite, tonalite, diorite and gabbro intruded into the center of Taknar zone. These intrusive rocks affected low grade metamorphism. The results of U-Pb zircon dating on two granite samples, one belonging to the Taknar mine west of the study area and the other the Bornaward granitoids in the eastern part of study area, and also one granodiorite the Taknar mine area and one diorite the Bornaward area, yield ages of the granites as 540.5±2.9 Ma (Taknar mine area) and 550.41 3.21,-4.54 Ma (Bornaward area), the granodiorite as 550±6.9 Ma and diorite as 551.96±4.32 Ma, all Late Neoproterozoic. The Bornaward intrusive bodies are classified as belonging to the ilmenite-series of reduced granitoids. Some small high magnetite-granite and tonalite outcrops in the study area are classified as belonging to the magnetite-series of oxidized granitoids. Chemically, most granitoids of the study area are S-type middle-high metaluminous to slightlymiddle peraluminous and belong to tholeiite, calc-alkaline to high-K calc-alkaline rock series with enrichments in LIL (Cs, Rb and Ba, U, K, Zr, Y, Th) elements and depletion in HIL (Sr and Nb, Ta, Ti) elements. Chondrite-normalized Rare Earth Elements (REEs) plots indicate minor enrichments of LREEs in comparison with HREEs, with (La/Yb)N between 1.04 -7.90 and total of REEs of the samples between 44.8 ppm (minimum) and 293.5 ppm (maximum) with strong negative anomaly of Eu compared to other Rare Earth elements. The Bornaward granitoid have an initial 87Sr/86Sr and 143Nd/144Nd ranging 0.703514 to 0.716888 and 0.511585 to 0.512061, respectively, when recalculated to an age of 550 to 538 Ma, consistent with the new radiometric age results. Initial εNd isotope values for granite, granodiorite and diorite range -6.73 to 2.52. TDM age of the BGC is 1.08-1.70 Ga. This indicates that the Bornaward granitoid complex (BGC) derived partial melting of distinct basement source regions with very high initial 87Sr/86Sr and underwent extensive crustal contamination.